Espaliers - Sydney Park Brown; Thomas H. Yeager; Robert J. Black (EDIS, 2013)
Illustrated publication by Sydney Park Brown, Thomas H. Yeager, and Robert J. Black, describes the technique of training plants against walls, fences, or trellises. It describes formal patterns, how to support, plant, and train them, general care, and trimming tips. Includes tables listing suggested trees, shrubs, and vines for espaliers in Florida. This version updated with new images.